Entre cestos e pregões: os trabalhadores ambulantes na cidade de São Paulo 1890-1910 - Camargo, Isabela do Carmo (2013)
The present work searches evidence concerning the presence and the experiences lived by street peddlers in the city of São Paulo, from 1890 to 1910, a period in which there were significant transformations in the capital of the state of São Paulo Brazil. There was the ending of slavery, the beginning of the republican regime and an outstanding population growth, mainly due to immigration. It analyses how street peddlers lived within the city modernization, and the aspects concerning their participation in supplying staples, as well as their relationship with the new rules established by the city, such as the taxing and license permits, which would then legitimate their activity as street peddlers are highlighted. The relationship and the conflicts among street peddlers and other subjects, such as their costumers, competing traders and the taxing system are also analyzed. In such analysis, it is noticed that street peddlers can be perceived in a perspective which overcomes the concept of marginality because they remain in the city in an intense way, working in spite of, sometimes, being watched in despise